Epidemiological Situation and Medical Management of Gynaecological and Breast Cancers from 1998 to 2018 in West Africa: A Systematic Review - Abdou Azaque Zoure; Bagora Bayala; Hierrhum Aboubacar Bambara; Alexis Yobi Sawadogo; Charlemagne Ouedraogo; Jean-Marc A. Lobaccaro; Jacques Simpore (Asian Pacific Journal of Cancer Biology, 2020)
Objective: Gynaecological cancers are public health diseases and contribute to the global burden of diseases. In West Africa most have been carried out on all gynaecological and breast cases to describe the epidemiological features and management modalities. Methods: Our research covered a period from 1998 to 2018. The terms “gynaecological cancers” and “West Africa”; are used to find records in the research databases (PubMed, ScienceDirect, Scopus and Google Scholar). There are countries (Cape Verde, Guinea, Gambia, Liberia, Sierra Leone) in which we have not found any work in the research databases. The process for selecting studies followed selection steps based on PRISMA 2009. Result: Cervical cancer is the commonest, followed by breast cancer, ovarian cancer, uterine or endometrial cancers, vaginal cancer and vulvar cancer. The lowest common was tubal cancers. The two English-speaking countries, Nigeria and Ghana, recorded 60 (60.82%) and 16 (15.68%) articles published respectively. At the same time, these two countries reported the most cases of gynaecological cancers including 72,848 cases (68.97%), 12, 327 cases (11.67%) and 12, 021 cases (11.38%) for Nigeria, Cote d’Ivoire and Ghana respectively. West Africa countries are characterised by poor outcome due to ignorance, superstition, self-denial, late presentation and unavailability of treatment facilities. Conclusion: Our study suggests that comprehensive national health insurance schemes as well as preventive strategies, patient and health work force education may improve the current situation. Also, West African countries must necessarily have a policy of acquiring the technical platforms to carry out these diagnostic and prognostic examinations.